Nitrous oxide emissions during establishment of eight alternative cellulosic bioenergy cropping systems in the North Central United States. Issue 3 (14th May 2015) - Oates, Lawrence G.; Duncan, David S.; Gelfand, Ilya; Millar, Neville; Robertson, G. Philip; Jackson, Randall D.
Abstract: Greenhouse gas (GHG) emissions from soils are a key sustainability metric of cropping systems. During crop establishment, disruptive land‐use change is known to be a critical, but under reported period, for determining GHG emissions. We measured soil N2 O emissions and potential environmental drivers of these fluxes from a three‐year establishment‐phase bioenergy cropping systems experiment replicated in southcentral Wisconsin (ARL) and southwestern Michigan (KBS). Cropping systems treatments were annual monocultures (continuous corn, corn–soybean–canola rotation), perennial monocultures (switchgrass, miscanthus, and poplar), and perennial polycultures (native grass mixture, early successional community, and restored prairie) all grown using best management practices specific to the system. Cumulative three‐year N2 O emissions from annuals were 142% higher than from perennials, with fertilized perennials 190% higher than unfertilized perennials. Emissions ranged from 3.1 to 19.1 kg N2 O‐N ha −1 yr −1 for the annuals with continuous corn > corn–soybean–canola rotation and 1.1 to 6.3 kg N2 O‐N ha −1 yr −1 for perennials. Nitrous oxide peak fluxes typically were associated with precipitation events that closely followed fertilization. Bayesian modeling of N2 O fluxes based on measured environmental factors explained 33% of variability across all systems. Models trained on single systems performed well in most monocultures (e.g., R 2  = 0.52 for poplar) but notably worse in polycultures (e.g., R 2  = 0.17 for early successional, R 2  = 0.06 for restored prairie), indicating that simulation models that include N2 O emissions should be parameterized specific to particular plant communities. Our results indicate that perennial bioenergy crops in their establishment phase emit less N2 O than annual crops, especially when not fertilized. These findings should be considered further alongside yield and other metrics contributing to important ecosystem services.